2021
DOI: 10.19105/iqtishadia.v8i2.4762
|View full text |Cite
|
Sign up to set email alerts
|

Peran Cash Waqfh Linked Sukuk (CWLS ) Dalam Optimalisasi Pemulihan Ekonomi Nasional Di Masa pandemi

Abstract: Abstract : This study aims to determine the role of Cash Waqf Linked Sukuk (CWLS) in optimizing the National Economic Recovery (PEN) during the Pandemic Period in Indonesia. The research method used in the research related to the role of Cash Waqf Linked Sukuk (CWLS) uses library research, this method is useful for collecting data, and the data can be from journals, web, news, and articles. other. This method does not involve interviews to collect data. This research was carried out as an effort t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This diagram summarizes the research approach used in research methodology related to CWLS in the scientific literature. It can be concluded that in the realm of research on CWLS, the dominant prevalence was found in the form of qualitative investigations in the form of literature studies with a percentage of 64.71% Afrianti, 2022;Anindhita et al, 2022;Armen et al, 2022;Cahyono et al, 2022;Hafandi et al, 2021;Indra et al, 2020;Istikomah et al, 2021;Lailatullailia et al, 2021;Maesarach et al, 2022;Mudriqoh, 2023;Mukti et al ., 2022;Nugroho et al, 2022;Puspitasari et al, 2022;Putri et al, 2020;Rahayu et al, 2020;Rahman et al, 2021;Maulina, 2022;Sa'idaturrohman , ;Sasongko et al, 2021;Siswantoro, ;Sulaeman et al, 2022;Tanjung & Agus, 2021 ;Ubaidilaah & Wahyu, 2021;Winarto et al, 2021; ANP (Afifah et al, 2022 ;Rabbani et al;Suratman et al, 2023) (Nurjamil, 2021), content analysis (Wati et al, 2022) and SLR Joseph, 2022).…”
Section: Cluster 4: Cwls Research Methodology (Additional)mentioning
confidence: 99%
“…This diagram summarizes the research approach used in research methodology related to CWLS in the scientific literature. It can be concluded that in the realm of research on CWLS, the dominant prevalence was found in the form of qualitative investigations in the form of literature studies with a percentage of 64.71% Afrianti, 2022;Anindhita et al, 2022;Armen et al, 2022;Cahyono et al, 2022;Hafandi et al, 2021;Indra et al, 2020;Istikomah et al, 2021;Lailatullailia et al, 2021;Maesarach et al, 2022;Mudriqoh, 2023;Mukti et al ., 2022;Nugroho et al, 2022;Puspitasari et al, 2022;Putri et al, 2020;Rahayu et al, 2020;Rahman et al, 2021;Maulina, 2022;Sa'idaturrohman , ;Sasongko et al, 2021;Siswantoro, ;Sulaeman et al, 2022;Tanjung & Agus, 2021 ;Ubaidilaah & Wahyu, 2021;Winarto et al, 2021; ANP (Afifah et al, 2022 ;Rabbani et al;Suratman et al, 2023) (Nurjamil, 2021), content analysis (Wati et al, 2022) and SLR Joseph, 2022).…”
Section: Cluster 4: Cwls Research Methodology (Additional)mentioning
confidence: 99%
“…Observations were carried out for approximately 3 months. Interviews were conducted with semi-structured techniques (Masduqie et al, 2021), to determine the production process of bottled drinking water. The data analysis techniques used in this study include data reduction, which focuses on the data obtained to answer a problem by sorting out valid, important, useful, interesting and renewable data (Sugiyono, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…The triangulation method chosen in this study is the triangulation of data sources, that is, certain information that is unearthed in order to find out the truth. Some information obtained from data sources through interviews and observations was then collected using the same technique (Winarto et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Langkah selanjutnya yaitu menganalisis secara kualitatif deskriptif. Analisis kualitatif deskriptif ialah analisis data yang berupa hasil dari dokumentasi, observasi, dan wawancara yang beruapa kata-kata saat wawancara langsunng melalui lisan maupun wawancara tidak langsung (Winarto et al, 2021). Untuk teknik penganalisan yaitu penelitian ini menggunakan teknik analisis data deskriptif, yaitu penelitian yang dimana penulis dapat meneliti dan menemukan informasi sebanyak-banyaknya mengenai objek yang akan diteliti (Herdiansyah, 2011).…”
Section: E Teknik Analisis Dataunclassified